HISTOLOGICAL ANALYSIS OF HEPATOPROTECTIVE EFFECTS OF EUGENIA UNIFLORA L. LEAF ETHANOLIC EXTRACT IN BALB/C MICE - JUWITA, DIAN AYU; RACHMAINI, FITRI; NASIF, HANSEN; MAYASARI, ELVI; ILAHI, REDHA (International Journal of Applied Pharmaceutics, 2025)
Objective: The plant Eugenia uniflora L. contains various bioactive compounds, including flavonoids, polyphenols, and terpenoids. These compounds can neutralize free radicals and reduce oxidative damage and inflammation in liver tissues, thereby potentially protecting the liver from damage caused by oxidative stress. The purpose of this study is to assess the effect of Eugenia uniflora L. Leaf Ethanolic Extract (EULEE) administration on the histopathological profile in male mice induced by carbon tetrachloride (CCl4). Methods: A total of 45 mice were assigned into 5 treatment groups, with 9 mice in each group. The negative control group was orally treated with Na-CMC suspension. The positive control group was treated orally with a 10% CCl4 solution. The treatment groups were administered a 10% CCl4 solution orally to induce hepatotoxicity, along with EULEE at doses of 200 mg/kg, 400 mg/kg, and 800 mg/kg BW. EULEE was administered for 7, 14, and 21 d. On days 8, 15, and 22, three mice from each treatment group were euthanized, and their liver organs were collected for histology analysis followed the Manja Roenigk Histopathology Scoring System. Statistical analysis was performed using two-way ANOVA. Results: The administration of EULEE 200, EULEE 400, EULEE 800 resulted in a reduction of liver histology scores compared to the positive control group, indicating a decrease in the level of liver tissue damage. The average histology scores for the three dosage groups were 39.556±0.0555, 47.600±0.555, and 45.333±0.555. Conclusion: The administration of EULEE results in an improvement in the liver's histological features in mice.